A relação entre os princípios do cooperativismo e o programa de inovação e de geração interna de ideias em uma cooperativa de crédito - Andrade, Theives Taine Feliz da Silva (2023)
The cooperativism is an economic system that produces and distributes wealth for groups with common interests, enabling advantages. Seven principles of cooperativism are the guidelines of this business model, orienting the actions and decisions made in these organizations. Given this, the objective of this study was to evaluate the relationship between the program of innovation and the internal generation of ideas in a credit cooperative. The methodology used is qualitative descriptive, carried out using a literature review, document analysis, questionnaires, and interviews with the proposal of a checklist, to evaluate the existing program with the person responsible for the analyzed area. The theoretical contribution of the research was given by the systematic literature review, which allowed the identification of 8 categories that most impact the realization of an internal program of ideas for innovation from experiences in Brazil and worldwide. The research's methodological contribution was given by presenting a data collection instrument developed from the seven principles of cooperativism, characteristics highlighted in the literature review, and recommendations of the ISO 56002/2019 standard - Innovation Management System. The instrument identifies necessary improvements in existing programs or can guide the implementation of programs that stimulate innovation in cooperatives. The practical contributions are verifying the relationship between the seven principles of cooperativism in the program of innovation and the internal generation of ideas and the proposition of actions to improve the program in the areas of investments, training, and communication. For future research, it is suggested to expand the surveyed public, including administrative and fiscal councils, in order to understand how these groups understand innovation, and with the cooperative members, to understand if they perceive the innovations in the use of systems and services at the branches. A quantitative study is also proposed, to evaluate the same phenomenon from the point of view of the possible influence that the implemented ideas may have on the economic performance of the cooperative.